Vibration energy transfer in track–subgrade systems with frequency-dependent rubber damping pads: A power flow analysis - Jin Chen; Shiyu Gong; Ruiyan Peng; Chengyue Wu; Bo Fu; Deliang Ma (Transportation Geotechnics, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Optimizing understory afforestation of shade-tolerant conifer Picea asperata across canopy transmittance gradients - Jing Jin; Haoran Wang; Zhidong Zhang; Yuan Gao; Qiang Liu; Lihua Fu; Dongsheng Chen; Lihu Dong; Hongtao Xie; Deliang Lu (European Journal of Forest Research, 2026)

Biodegradation performance of azo dyes based on Fe-Mn@C dual-template molecularly imprinted sensor - Qikai Fu; Deliang Guo; Xiaoyu Zhang; Xiongfang An; Xiaolin Xu (Journal of Environmental Sciences, 2026)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

Spermatogenesis and ultrastructure of the spermatozoa at three ploidy levels in the bivalve species, Corbicula fluminea - Jie Pi; Yangxin Tang; Ying Fu; Xu Wang; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Tissue and Cell, 2025)

Chrysalis-inspired high-toughness low-modulus conductive hydrogel sensor for intelligent sensing - Yugui Cheng; Simian Fu; Kaiming Jin; Yiying Liu; Jingtong Ma; Deliang Li; Qingying Lyu; Yehan Li; Xiaoyang Jiang; Ruonan Liu; Ye Tian (Chemical Engineering Journal, 2024)

Integrated tea polyphenols and polydopamine functionalized graphene anode for improved bioelectricity generation and Cr(VI) reduction in microbial fuel cells - Deliang Guo; Xinru Wang; Qikai Fu; Ling Li; Runze Li; Xiaolin Xu; Xiongfang An (Chemosphere, 2024)

Antifreeze protein-based ultrastretchable and highly sensitive hydrogel for human-machine interaction - Zhiwei Fu; Deliang Li; He Liu; Ruonan Liu; Qingying Lyu; Yixuan Han; Yanpeng Wang; Kai Zhang; Guanglei Chen; Ye Tian (Chemical Engineering Journal, 2024)

Associations between prenatal exposure to polycyclic aromatic hydrocarbons and thyroid hormones in umbilical cord blood - Xiyuan Yao; Yidong Wang; Yifei Ma; Mengmeng Fu; Huimin Wang; Deliang Tang; Jisheng Nie (Environmental Science and Pollution Research, 2023)

Diesel soot combustion over ceria catalyst: Evolution of functional groups on soot surfaces - Jiangjun Wei; Chenyang Fan; Yuan Zhuang; Zheng Fu; Ze Guan; Haizhao Li; Deliang Li; Yejian Qian (Fuel, 2023)

Photoperiod drives cessation of wood formation in northern conifers - Wenhuan Mu; Xiuchen Wu; J. Julio Camarero; Yongshuo H. Fu; Jianguo Huang; Xiaoyan Li; Deliang Chen (Global Ecology and Biogeography, 2023)
Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation ( C cw ) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐three conifer species. Methods A generalized additive model was fitted to characterize the latitudinal pattern in C cw . Structural equation modelling and a linear mixed‐effects model were applied to determine the main drivers underlying the latitudinal pattern in C cw . Results The C cw followed a flat S‐shaped pattern with increasing latitude. Photoperiod was the dominant determinant of the latitudinal pattern of C cw , and a longer photoperiod was associated with an earlier C cw . Both mean growing‐season temperature and total growing‐season precipitation exhibited significantly positive relationships to the cessation of cell elongation and thus the C cw across all study sites. In arid regions, the pre‐growing‐season temperature had a significantly negative effect on C cw . In humid regions, C cw was positively affected by the mean growing‐season temperature. The onset of wood formation showed significantly positive coupling with C cw at arid sites but not at humid sites. Early successional species were sensitive to hydrothermal variations during the pre‐growing season. Main conclusions We reveal the dominant role of photoperiod in determining the cessation of wood formation for northern conifers and highlight differentiated interactive effects between photoperiod and seasonal climatic factors and the preceding xylem phenophases in determining C cw among ecoregions and tree species. These insights provide evidence to reduce uncertainty in prediction of the forest carbon uptake potential and the consequent biophysical feedbacks of northern forests.

Growth of winter wheat adapting to climate warming may face more low‐temperature damage - Yanling Song; Guangsheng Zhou; Hans W. Linderholm; Junfang Wang; Yong Li; Guofu Wang; Yan Fu; Jinxia Xu; Ying Shi; Ying Xu; Hui Gao; Deliang Chen (International Journal of Climatology, 2023)
China's surface air temperature is increasing due to global warming, so it is interesting that how low temperatures would be changed during the growth period of winter wheat in future. We focused on the low temperatures of winter wheat from 2021 to 2050, using temperatures under the high emission scenario Representative Concentration Pathway 8.5 (RCP8.5) projected by the RegCM4.4 regional climate model. The results showed that the annual mean temperature was projected to increase by 0.42°C⋅decade −1 in the northern and by 0.35°C⋅decade −1 in the southern winter wheat region. Furthermore, the temperature was expected to increase rapidly in spring, which could advance the dates of flowering and the start of the grain‐filling period. Using the genetic parameters determined by the calibration and validation of WOFOST and bias‐corrected projected meteorological data, simulations of winter wheat growth were performed over the winter wheat region for 2021–2050. The simulated number of days to the flowering period of winter wheat for 2041–2050 was on average 6.5 days less than in 2021–2030, due to the spring warming. Because of the earlier start of the growing season, winter wheat could face negative effects by being subjected to low temperatures. Indeed, the number of low‐temperature days was projected to increase by 110% from 2041 to 2050 compared to 2021–2030, and the number of killing degree days (KDDs) is projected to increase by 120% at the same time. If the number of days to flowering did not change, the number of low‐temperature days and KDDs only changed slightly, showing that the negative influence of low temperature was mainly caused by the advancement of the flowering date. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered.

Geochemical characteristics of shales from Upper Carboniferous Yanghugou formation in Weiningbeishan area, China: Implication for provenance, source weathering and tectonic setting - Yu Ma; Hongze Yang; Yanyun Ma; Yongping Wang; Wenzhong Wu; Na An; Shuofeng Tian; Ling Ma; Deliang Fu (Marine and Petroleum Geology, 2023)

The current study and development of organic matter pores in organic-rich shale - Lina Sun; Deliang Fu; Yuandong Wu; Zixiang Wang (Arabian Journal of Geosciences, 2022)

The performance of CORDEX-EA-II simulations in simulating seasonal temperature and elevation-dependent warming over the Tibetan Plateau - Xiaorui Niu; Jianping Tang; Deliang Chen; Shuyu Wang; Tinghai Ou; Congbin Fu (Climate Dynamics, 2021)
To explore the driving mechanisms of elevation-dependent warming (EDW) over the Tibetan Plateau (TP), the output from a suite of numerical experiments with different cumulus parameterization schemes (CPs) under the Coordinated Regional Climate Downscaling Experiments-East Asia (CORDEX-EA-II) project is examined. Results show that all experiments can broadly capture the observed temperature distributions over the TP with consistent cold biases, and the spread in temperature simulations commonly increases with elevation with the maximum located around 4000–5000 m. Such disagreements among the temperature simulations could to a large extent be explained by their spreads in the surface albedo feedback (SAF). All the experiments reproduce the observed EDW below 5000 m in winter but fail to capture the observed EDW above 4500 m in spring. Further analysis suggests that the simulated EDW during winter is mainly caused by the SAF, and the clear-sky downward longwave radiation (LW clr ) plays a secondary role in shaping EDW. The models’ inability in simulating EDW during spring is closely related to the SAF and the surface cloud radiative forcing (CRFs). Furthermore, the magnitude and structure of the simulated EDW are sensitive to the choice of CPs. Different CPs generate diverse snow cover fractions, which can modulate the simulated SAF and its effect on EDW. Also, the CPs show great influence on the LW clr via altering the low-level air temperature. Additionally, the mechanism for different temperature changes among the experiments varies with altitudes during summer and autumn, as the diverse temperature changes appear to be caused by the LW clr for the low altitudes while by the SAF for the middle-high altitudes.

Development mechanism of organic-inorganic composite pores in the shale of the Niutitang Formation at the Huijunba syncline - Fu Deliang; Sun Lina; Li Jing; Wang Zixiang; Tian Tao; Yao Jianming; Duan Zhonghui; Yang Fu (Arabian Journal of Geosciences, 2021)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

Late Ordovician provenance and depositional setting in the southwestern Ordos Block, China: constraints from zircon U-Pb geochronology - Fu Yang; Gang Chen; Yu Kang; Dongmin Ma; Qilin Chen; Tian Tao; Fu Deliang (Geosciences Journal, 2020)

On the sensitivity of seasonal and diurnal precipitation to cumulus parameterization over CORDEX-EA-II - Xiaorui Niu; Jianping Tang; Shuyu Wang; Congbin Fu; Deliang Chen (Climate Dynamics, 2020)

Characterization and controlling factors of pores in the Lower Cambrian Niutitang shale of the Micangshan Tectonic Zone, SW China - Tao Tian; Shixin Zhou; Deliang Fu; Fu Yang; Jing Li (Arabian Journal of Geosciences, 2019)

Improved Land Use and Leaf Area Index Enhances WRF-3DVAR Satellite Radiance Assimilation: A Case Study Focusing on Rainfall Simulation in the Shule River Basin during July 2013 - Junhua Yang; Zhenming Ji; Deliang Chen; Shichang Kang; Congshen Fu; Keqin Duan; Miaogen Shen (Advances in Atmospheric Sciences, 2018)

Comparison between two statistical downscaling methods for summer daily rainfall in Chongqing, China - Lijun Fan; Zhongwei Yan; Deliang Chen; Congbin Fu (International Journal of Climatology, 2015)
Two circulation index‐based methods were applied to downscale summer daily rainfall at four meteorological stations in Chongqing, China. One is a regression method ( CIM ) and the other a hybrid circulation classification plus regression method ( CPM ). Both methods used the same three circulation indices and surface specific humidity as predictors. In the first method ( CIM ), the indices and humidity were used directly as predictors and only one model was developed at each station. In the second method ( CPM ), the indices were further used to define circulation patterns using the objective Lamb‐Jenkinson classification scheme, and one model was built using humidity as the sole predictor for each pattern. Logistic regression was used to define rainfall probability, and a gamma distribution was fit using observations to randomly generate daily rainfall amounts. The two downscaling methods were validated and compared. The results suggest that (1) both methods yield consistently reasonable results with respect to occurrence and amount of daily rainfall, although they perform poorly in reproducing interannual and interdecadal variability, (2) specific humidity should be used as a predictor. Both methods were forced by two future scenarios of a global climate model ( GCM ) to demonstrate the added value with two methods. The downscaled scenarios show a shift towards larger rainfall values, accompanied by more frequent dry days. This shift is mainly attributed to a change in specific humidity. Despite the similar performances of the two methods, CPM gives a higher frequency of dry days than CIM , whereas CIM produces stronger intensity of rainfall than CPM . This provides additional information about the uncertainty in the projections.

Statistical downscaling of summer temperature extremes in northern China - Lijun Fan; Deliang Chen; Congbin Fu; Zhongwei Yan (Advances in Atmospheric Sciences, 2013)

Trends in graded precipitation in China from 1961 to 2000 - Jiaolan Fu; Weihong Qian; Xiang Lin; Deliang Chen (Advances in Atmospheric Sciences, 2008)